(untitled) (Estudos em Design, 2025)
Editores Cristina Portugal Rita Couto Avaliadores desta edição V. 33, n. 3 (2025) Adriana Gralow Adriana Sampaio Leite Aline Savi Álvaro Sousa Ana Berwanger André Ribeiro de Oliveira Andréa Almeida Antonio Colchete Filho Artur Mottin Beany Monteiro Bruno Serviliano Farias Carlo FranzatoCarolina Vaitiekunas Pizarro Cassia Carrara Domiciano Cassia Furtado Cyntia Malaguti de Sousa Daniel Portugal Daniel Raposo Edson Rufino Elizabeth Romani Everton da Silva Fabiane Fernandes Fábio Caparica de Luna Fausto Medola Felipe Santos Felipe Viaro Fernando Fogliano Frederico Braida Gabriel Patrocinio Joana Contino Kando Fukushima Luiza Falcão Soares Cunha Marcio Guimarães Maria Clara Aquino Maria Do Carmo Gonçalves Curtis Marilda Lopes Pinheiro Queluz Maria Teresa Lopes Marina Kunst Maurício Klafke Dick Olavo Neto Otniel Altamirano Patrícia dos Santos Rafaela Sarinho Rafaella Peres Ravi Passos Rogério Camara Seila Sitta Preto Sérgio Luciano da Silva Tomás Barata Tiago Silva Verônica Freire